SILATRANE-CONTAINING POLYMETHACRYLATES - V. V. Istratov; E. V. Andreeva; V. I. Gomzyak; V. A. Vasnev (Тонкие химические технологии)
The possibility of synthesizing silatrane-containing polymers was investigated using three different synthetic methods: the formation of silatrane fragments from polymers with trialkoxysilyl groups, the copolymerization of silatrane-containing monomers, and the reaction of silatranes with functional copolymers. The obtained polymethacrylate copolymers were characterized using gel permeation chromatography, IR and NMR spectroscopy. It was shown that depending on the synthesis scheme used, polymers were obtained in the form of three-dimensional structures or soluble products. It was established that the molecular weight of the synthesized polymers depended significantly on both the content of silatrane fragments and the synthesis technique used. It was shown that the modification of linear carboxyl-containing copolymers by silatranes allows the synthesis of high-molecular polymers with a high content of silatrane fragments. For the synthesized polymers, thermal properties were investigated, and the hydrophobicity of the surface of polymer films was also evaluated. It was found that all the studied polymers did not have clear melting and crystallization temperatures. The polymers were stable in an inert atmosphere up to 270-280 °C, whereas in air they decomposed at lower temperatures with the restructuring of the macromolecular skeleton and the formation of highly heat-resistant silicone structures. An increase in the content of silatrane moieties in the copolymers led to an increase in the hydrophilicity of polymers.